Relationships between upper airway dimensions and mandibular morphology and position – a review - Paluch, Zbigniew; Stelmańska, Karolina; Twardokęs, Marta; Gamrot-Wrzoł, Marta (Journal of Stomatology, 2015)
Introduction. Reviews of the literature on morphometrics of upper airway (UA) dimensions and facial skeleton have been presented. However, there have been no study reviews on the relationship between UA morphometrics and mandibular morphometrics. Aim of the study. To perform a systematic review of the literature on the relationships between morphometric measurements of UAs and mandibular morphometrics. The authors searched for differences between UA dimensions in various patterns of the facial skeleton. Material and methods. The selected articles were divided into three groups: 1) the relationship of skeletal and/or dental Class II with UA dimensions, 2) the relationship of skeletal and/or dental Class III with UA dimensions, 3) the relationship of the measurements of the Gonial angle and mandibular length with UAs. Discussion. The authors indicated a tendency towards smaller UA dimensions in mandibular retrognathic subjects. Studies indicated larger dimensions of both upper and lower pharynx in the sample with skeletal Class III compared to the dimensions in skeletal Class I. Summary. The review of the literature confirms the relationship between mandibular morphology and position and particular UA dimensions in the studied samples. Based on the available knowledge, it would be possible to adjust a treatment method influencing not only the improvement in relation between the mandible and the adjacent structures, especially superior and inferior dental arches, but also considering UA dimensions in respective skeletal classes.